Anatomical Transcriptome Atlas of the Male Mouse Reproductive System During Aging - Huang, Yanping; Li, Xiangping; Sun, Xiangzhou; Yao, Jiahui; Gao, Fengxin; Wang, Zhenqing; Hu, Jiaying; Wang, Zhu; Ouyang, Bin; Tu, Xiangan; Zou, Xuenong; Liu, Wei; et al. (Frontiers in Cell and Developmental Biology, 2022)
The elderly males undergo degenerative fertility and testicular endocrine function that jeopardize the reproductive health and well-being. However, the mechanisms underlying reproductive aging are unclear. Here, we tried to address this by investigating the phenotypes and transcriptomes of seven regions of the male mouse reproductive tract: the testis, efferent ductules, initial segment, caput, corpus and cauda epididymidis, and vas deferens, in adult (3 months) and aged (21 months) mice. Quantitative PCR, immunohistochemistry, immunofluorescent staining, and enzyme-linked immunosorbent assay were performed for the analysis of gene expression in mice, human tissues, and semen samples. Aged male mice showed both systematic and reproductive changes, and remarkable histological changes were detected in the testis and proximal epididymis. Transcriptomes of the male reproductive tract were mapped, and a series of region-specific genes were identified and validated in mouse and/or human tissues, including Protamine 1 (Prm2), ADAM metallopeptidase domain 28 (Adam28), Ribonuclease A family member 13 (Rnase13), WAP four-disulfide core domain 13 (Wfdc13), and Wfdc9. Meanwhile, age-related transcriptome changes of different regions of the male reproductive tract were characterized. Notably, increased immune response was functionally related to the male reproductive aging, especially the T cell activation. An immune response-associated factor, phospholipase A2 group IID (Pla2g2d), was identified as a potential biomarker for reproductive aging in mice. And the PLA2G2D level in human seminal plasma surged at approximately 35 years of age. Furthermore, we highlighted Protein tyrosine phosphatase receptor type C (Ptprc), Lymphocyte protein tyrosine kinase (Lck) , Microtubule associated protein tau (Mapt), and Interferon induced protein with tetratricopeptide repeats 3 (Ifit3) as critical molecules in the aging of initial segment, caput, caput, and cauda epididymidis, respectively. This study provides an RNA-seq resource for the male reproductive system during aging in mice, and is expected to improve our understanding of male reproductive aging and infertility.